(untitled) (Journal of Information Technologies in Education (ITE), 2009)
The article presents the collective experience of staff research institute of information technology to KSU for the Ministry of Education and Science of Ukraine, scientific and technical work, the result of which will be creating an Internet portal ECDL distance learning for higher education.